2021
DOI: 10.1038/s41598-021-81770-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercise on macular vessel density and choroidal thickness in children

Abstract: We used swept-source (SS) optical coherence tomography (OCT) and OCT angiography (OCTA) to investigate the effects of moderate physical exercise on retinal and choroidal vessel densities (VDs) and thicknesses in children. One eye in each of 40 myopic children (mean age, 11.70 years) and 18 emmetropic children (mean age, 11.06 years) were included. SS-OCT 6 × 6-mm radial scans and SS-OCTA 3 × 3-mm images were centered on the macula. Heart rate (HR), systolic and diastolic blood pressure, and intraocular pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Similar to the findings in young adults, we could not observe any correlation between retinal and choroidal thickness changes postexercise; also, there was no obvious trend in choroidal changes in this period due to the large deviation of the measurements. Some studies have found a significant decrease in macular and optic nerve head flow density along with a decreased vascular density in the deep retinal layers of myopic eyes (Alnawaiseh et al, 2017), and increased vascular density was detected following 30 min of rest after physical exercise in the whole retina in children with myopia and emmetropia as well (Li et al, 2021). These observations could also explain the trend toward an acute thinning of the retina observed postexercise in our cohort.…”
Section: Discussionsupporting
confidence: 63%
“…Similar to the findings in young adults, we could not observe any correlation between retinal and choroidal thickness changes postexercise; also, there was no obvious trend in choroidal changes in this period due to the large deviation of the measurements. Some studies have found a significant decrease in macular and optic nerve head flow density along with a decreased vascular density in the deep retinal layers of myopic eyes (Alnawaiseh et al, 2017), and increased vascular density was detected following 30 min of rest after physical exercise in the whole retina in children with myopia and emmetropia as well (Li et al, 2021). These observations could also explain the trend toward an acute thinning of the retina observed postexercise in our cohort.…”
Section: Discussionsupporting
confidence: 63%
“…In some studies, macular perfusion and retinal vascular density were reported to decrease significantly after exercise [ 39 , 42 ] which may explain the acute thinning of the choroid just after the physical strain. In our study, after the trend for acute thinning in the first post-exercise minute, we observed a thickening trend at 5 minutes, followed by another thinning trend at 30 minutes and then a slow thickening again, which may refer to an extended choroidal reaction and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, after the trend for acute thinning in the first post-exercise minute, we observed a thickening trend at 5 minutes, followed by another thinning trend at 30 minutes and then a slow thickening again, which may refer to an extended choroidal reaction and regeneration. Li et al also reported a decrease in choroidal thickness after moderate physical activity that lasted for at least 30 minutes; however, they did not examine the first 10 minutes of the recovery period [ 42 ]. The dilatation or contraction of the vascular or non-vascular smooth muscles of the choroid may modulate the blood flow [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choroid is a highly vascularized tissue, which makes it more suspectable to inflammation and ischemia-associated systemic disorders. A reduction in ChT following exercise might be related to an exercise-induced decrease in the flow of the internal carotid artery 37 . Regarding weakly significant results of this study, it can be postulated that temporal and partial nasal choroidal thinning in the pediatric COVID-19 patients may be related to blood flow reduction due to SARS-CoV-2 caused hypercoagulability and vasculitis 38 .…”
Section: Discussionmentioning
confidence: 99%